TECHNICAL IMPLEMENTATION OF CLOUD-DRIVEN MOBILE INSURANCE SERVICES: A COMPREHENSIVE ANALYSIS - Veera Venkata Ramana Murthy Bokka (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive technical article examines the transformation of insurance services through the integration of cloud computing and mobile technologies. The article investigates the implementation of microservices architecture, multi-layered security frameworks, advanced analytics, and mobile application architectures in modern insurance platforms. The article demonstrates how cloud-based solutions have revolutionized operational efficiency, risk assessment, and customer service delivery while ensuring robust security and regulatory compliance. The article covers the deployment of sophisticated data processing pipelines, machine learning models for fraud detection, and innovative edge computing solutions. The article reveals significant improvements in system reliability, processing efficiency, and user experience, establishing a foundation for future technological advancement in the insurance industry.